A Trace of Vice (a Keri Locke Mystery--Book #3) - Blake, Pierce (Lukeman Literary, 2017)
"A dynamic story line that grips from the first chapter and doesn't let go." --Midwest Book Review, Diane Donovan (regarding Once Gone) From #1 bestselling mystery author Blake Pierce comes a new masterpiece of psychological suspense. In A TRACE OF VICE (Book #3 in the Keri Locke mystery series), Keri Locke, Missing Persons Detective in the Homicide division of the LAPD, follows a fresh lead for her abducted daughter. It leads to a violent confrontation with The Collector-which, in turn, offers more clues that may, after all this time, reunite her with her daughter. Yet at the same time, Keri is assigned a new case, one with a frantic ticking clock. A teenage girl has gone missing in Los Angeles, a girl from a good family was who duped into drugs and abducted into a sex trafficking ring. Keri is hot on her trail-but the trail is moving fast, with the girl being constantly moved and with her abductors' single, nefarious goal: to cross her over the border with Mexico. In an epic, breathtaking, cat and mouse chase that takes them through the seedy underworld of trafficking, Keri and Ray will be pushed to their limits to save the girl-and her own daughter-before it is all too late. A dark psychological thriller with heart-pounding suspense, A TRACE OF VICE is book #3 in a riveting new series-and a beloved new character-that will leave you turning pages late into the night. "A masterpiece of thriller and mystery! The author did a magnificent job developing characters with a psychological side that is so well described that we feel inside their minds, follow their fears and cheer for their success. The plot is very intelligent and will keep you entertained throughout the book. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) Book #4 in the Keri Locke series will be available soon.
Keywords: Krimi, detektivky